Cross cultural perspectives in child advocacy - Berson, Ilene R.; Berson, Michael J.; Cruz, Bárbara C. (Emerald Publishing Limited : Information Age Publishing, 2001)
This study on cross cultural perspectives in child advocacy deals with various topics, including support for children's issues, the factors that influence reporting of suspected child abuse and child advocacy's application to education professionals. The study looks at issues from around the world.
Keywords: Children's rights.; Children's rights -- Cross-cultural studies.; Child welfare -- Cross-cultural studies.; Social advocacy -- Cross-cultural studies.; Law -- Child Advocacy.; Child welfare and youth services.; Family law: children.; Legal skills: advocacy.; elektronické knihy; electronic books